(untitled) - Roll, Martin (New York, N.Y., 2006)
Asian Brand Strategy offers insights, knowledge and perspectives on Asian brands and branding as a strategic tool and provides a comprehensive framework for understanding Asian branding strategies and Asian brands, including success stories and challenges for future growth and strengths. The book includes theoretical frameworks and models and up-to-date case studies on Asian brands, and it a must-read for Asian and Western business leaders as well as anyone interested in the most exciting region of the world. The book presents the Asian Brand Leadership model illustrating the paradigm shift Asian brands need to undertake to unleash their potential. First, mindsets and practices need to change in the Asian boardroom. The book invites a complete shift in the way Asian boardrooms think of branding: from a tactical view to a long-term, strategic perspective, from fragmented marketing activities to totally aligned branding activities, from a vision of branding as the sole responsibility of marketing managers to branding as the most essential function of the firm led by the boardroom.
Keywords: Brand name products,Brand name products; Management,Marketing; Asia,Asia